STANDARD AKUNTANSI PERSEDIAAN: BENARKAH IFRS MENGGUNAKAN PRINCIPLES-BASED DAN US GAAP MENGGUNAKAN RULES-BASED? - Sururi . (Akademi Akuntansi YKPN Yogyakarta, 2009)
IFRS and US GAAP are two mainstream of accounting standards which are deeply affect the accounting practices internationally. The IFRS is said as “principles-based” in nature and the US GAAP at the opposite side as “rules-based” in nature. Although gradually the influence of IFRS is outperform the US GAAP, but most of the US GAAP users still having difficulties in familiarizing with IFRS. The term of “principles-based” and “rules-based” to differentiate the two mainstream of accounting standards seem to be used as a simplification in viewing the difference between the both standards. Principles-based means that the accounting standards is not rigid, they are only providing general guideline on how the standards should be applied, on the other side the term rules-based means that the standards are the rigid rules of accounting practice. This paper is aimed to prove the appropriateness of the term “principles-based” for the IFRS and “rules-based” for the US GAAP, particularly in the case of accounting standards for inventory.Keywords: IFRS, US GAAP, principles-based, rules-based